Effects of salt stress on antioxidant and ascorbate glutathione cycle enzyme activities in Pokkali rice varieties – Vytilla 1-9 - Simon, Lins; Yusuf, Akkara (Plant Science Today, 2020)
The enzymatic and non-enzymatic antioxidant levels in the released salt tolerant Pokkali, (vytilla, VTL 1-9) varieties were studied under different NaCl concentrations (0-150 mM NaCl). The specific activity of superoxide dismutase (SOD), catalase (CAT) and ascorbate-glutathione cycle enzymes and non-enzymatic antioxidants like superoxide (O2-), hydrogen peroxide (H2O2), malondialdehyde (MDA), glutathione (GSH) and ascorbic acid (AsA) was determined in plants exposed to salt stress. IR-28 was used as positive control and the VTL varieties were used as negative control. The H2O2 and superoxide (O2-) contents were higher in IR-28 at all the applied concentrations of NaCl. The VTL varieties without salt treatment did not evoke any response substantiating the role of salt priming in antioxidant signalling. The MDA contents were higher in the positive and negative control. MDA content was reduced in the NaCl treated VTL varieties. In the positive and negative control varieties, the quantity of ascorbate and glutathione contents were lesser and upregulated in salt treated VTL varieties. Highest H2O2 content was observed in 150 mM NaCl treatment. The H2O2 contents decreased with the increase in all concentrations of NaCl and lowest H2O2 contents was observed in VTL-1 and highest in VTL-2 and VTL-8 treated with 150 mM NaCl. Superoxide contents varied in all the nine varieties depending on the salt concentration. The SOD levels in all the varieties showed a positive correlation with the superoxide and H2O2 content. Lesser quantities of SOD, CAT and the ascorbate - glutathione cycle enzymes were expressed in the positive and negative control. The increased NaCl concentration (25-150 mM) upregulated antioxidant and ascorbate-glutathione cycle enzymes in the VTL varieties. The APX activity was lower in the control and salt treated plants. The GR activity increased linearly in all the varieties with respect to salt concentrations. The MDHAR and DHAR activities showed marginally linear increase, with all concentrations of NaCl. The APX activity was similar or lower to MDHAR activity while DHAR activity was similar to MDHAR activity. The results of the present study reveals the higher levels of enzymatic and non-enzymatic antioxidants under salt stress reflect the salt tolerance potential of pokkali varieties mediated by the up regulation of ROS scavenging enzymes.